Giải các pt sau:
a) \(\sqrt{x+8}+\frac{9x}{\sqrt{x+8}}-6\sqrt{x}=0\)
b) \(x^4-2x^3+\sqrt{2x^3+x^2+2}-2=0\)
c) \(3x\sqrt[3]{x+7}\left(x+\sqrt[3]{x+7}\right)=7x^3+12x^2+5x-6\)
d) \(4x^2+\left(8x-4\right)\sqrt{x}-1=3x+2\sqrt{2x^2+5x-3}\)
e) \(16x^2+19x+7+4\sqrt{-3x^2+5x+2}=\left(8x+2\right)\left(\sqrt{2-x}+2\sqrt{3x+1}\right)\)
f) \(\left(5x+8\right)\sqrt{2x-1}+7x\sqrt{x+3}=9x+8-\left(x+26\right)\sqrt{x-1}\)
g) \(\sqrt[3]{3x+1}+\sqrt[3]{5-x}+\sqrt[3]{2x-9}-\sqrt[3]{4x-3}=0\)
Giải phương trình:
a) \(x^3-3x^2-9x+12=0\)
b) \(\left(x-3\right)^4+\left(x+1\right)^4=82\)
c) \(x^4-10x^3+25x^2-20x+4=0\)
d) \(2x^4+12x^3+7x^2-33x+5=0\)
e) \(\left(x^2-3x+3\right)^2-3x^2+8x-6=0\)
f) \(\left(x-3\right)\left(x-1\right)\left(x+2\right)\left(x+6\right)-40x^2=0\)
1. giải phương trình bậc hai một ẩn
a, 3x2+7x+2=0
b,\(\dfrac{x^2}{3}+\dfrac{4x}{5}-\dfrac{1}{12}\)=0
c\(\left(5-\sqrt{2}\right).x^2-10x+5x+\sqrt{2}=0\)
d,(x-1)(x+2)=70
Giải các phương trình sau:
a) \(2x^4-x^3-6x^2-x+2=0\)
b) \(\left(x+1\right)\left(x+2\right)\left(x+3\right)\left(x+4\right)=24\)
c) \(x^4-4x^3+3x^2+2x-6=0\)
Giải phương trình:
1, \(\left(x^2+x+1\right)\left(x^4+2x^3+7x^2+26x+37\right)=5\left(x+3\right)^3\)
2, \(\left(x+1\right)^3+\left(x+3\right)^3+6\left(x+1\right)\left(x+7\right)\left(x+3\right)=8\left(x+2\right)^3\)
3, \(x^3+\left(x-1\right)^3+3x\left(x-1\right)\left(x^4+x\right)=\left(2x-1\right)^3\)
4, \(\dfrac{\left(x+1\right)^3}{3x+1}+\dfrac{x^3+5x+2}{x^3+2x+1}=x+3\)
5, \(\dfrac{5x^3+x^2+x+1}{4x^2+1}+\dfrac{6\left(4x^2+1\right)}{x^3+x^2+1}=x+7\)
6, \(\left(x^2-4x+1\right)^3+\left(8x-x^2+4\right)^3+\left(x-5\right)^3=125x^3\)
Giải phương trình 1, \(x^2+9x+7=\left(2x+1\right)\sqrt{2x^2+4x+5}\)
2, GPT \(\left(2x+7\right)\sqrt{2x+7}=x^2+9x+7\)
3. GHPT \(\left\{{}\begin{matrix}x^2-2y-1=2\sqrt{5y+8}+\sqrt{7x-1}\\\left(x-y\right)\left(x^2+xy+y^2+3\right)=3\left(x^2+y^2\right)+2\end{matrix}\right.\)
Giải các phương trình sau:
1. \(x^4-4x^3-6x^2-4x+1=0\)
2. \(x^4-4x^2+12x-9=0\)
3. \(x^4-4x=1\)
4. \(\left(x+2\right)\left(x+3\right)\left(x+8\right)\left(x+12\right)=4x^2\)
5. \(x^4+4x^3+3x^2+2x-1=0\)
Giải các phương trình sau
a) \(2x^4-x^3-6x^2-x+2=0\)
b) \(\left(x+1\right)\left(x+2\right)\left(x+3\right)\left(x+4\right)=24\)
Giải PT
\(\left(x-1\right)\left(x-3\right)\left(x+5\right)\left(x+7\right)=297\)
\(x^4-8x^2+x+12=0\)
\(x^4+5x^3-10x^2+10x+4=0\)
\(\left(6x^2-5x+1\right)\left(x^2-5x+6\right)=4x^2\)